Passive, semi-active, active and hybrid mass dampers: A literature review with associated applications on building-like structures - Koutsoloukas, Lefteris; Nikitas, Nikolaos; Aristidou, Petros (My University, 2022)
In this paper, a state-of-the-art literature review is presented emphasising on the development of control variants for mass damper schemes on building-like structures. Additionally, a systematic literature review is conducted addressing three relevant questions: What type of mass damper is preferable by the associated industry? How are mass dampers distributed around the world? Is industry following research? Through the systematic literature review, updated lists of mass damper implementations and control algorithm applications in real-life structures were compiled. 208 case-studies are discussed in total. It is found that, 63% of them refer to passive tuned mass dampers, 31% to hybrid mass dampers, 4.0% to active mass dampers and only 2% to semi-active mass dampers. Regarding control algorithms, controllers of 24 structures driving semi-active, active or hybrid mass dampers are presented. It is concluded that the industry considerably lags behind latest structural control research both regarding implementations and overall management.
Keywords: Control algorithms; Passive control; Semi-active control; Active control; Hybrid control; Control applications; Tall buildings; Vibration control; Systematic review